Influence of electric field on direct and indirect exciton in a concentrically coupled quantum ring heterostructure embedded in SiO2 matrix. (January 2020) - Sherly, I. Janet; Nithiananthi, P.
Abstract: Excitonic states of Concentric Double Quantum Ring (CDQR) heterostructures embedded in SiO2 matrix under the influence of electric field has been calculated theoretically using variational technique. CDQR has been confined in a quantum well of suitable width which serve as the height of the quantum ring along which the electric field is applied. Central barrier width, outer ring width and carrier location has been tuned to understand the localization of both direct and indirect excitons. Effect of ring dimension and electric field on the energy states of Inner Ring Exciton (IRE) and Outer Ring Exciton (ORE) has been determined. Tilting of conduction and valence bands due to the application of electric field invokes a triangular confinement to the carriers and the same has been discussed. Diamagnetic susceptibility which is merely an indicator of electron hole separation and intersubband transition energy has also been calculated for both symmetric and asymmetric quantum ring. Height of the QR has also been changed to study its effect on the diamagnetic susceptibility of an exciton. Highlights: Enclosure of ligand in a quantum ring promotes higher carrier stability. Application of electric field reduces localization of exciton in a ring. Inter-particle separation is measured through diamagnetic susceptibility. Conspicuous change in localization and χdia is observed when OR ≈ IR . Tuning ring dimension facilitates the transformation of direct exciton to indirect.